NILAI-NILAI KESUFIAN PADA PUISI “AKU INGIN” KARYA SAPARDI DJOKO DAMONO - Sohib Sohib; Desah Pratiwi; Agus Priyanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This article disceuses about “Kesufian” values on “Aku ingin” poem by Sapardi Djoko Damono, the discussion will be seen on some as pects, they are semiotic with seeing the signs in each diction. Beside that, the discussion about “Kesufian” values. The understanding about values is based on “Journey” concept. “Salik” journey in reaching step by step of “Maqam”. At the end of “Aku ingin” poem, it can be seen “Journey” concept becomes “Kesufian” values that standing on abolition selp (hulul) or concept (wahdatul wujud). Finally, will be found the unity of plot idea that refers to “Kesufian” values that effecting the whole text.